2022
DOI: 10.1002/cpp.2726
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the therapeutic alliance in psychotherapy and suicidal experiences: A systematic review

Abstract: It is well established that there is a fundamental need to develop a robust therapeutic alliance to achieve positive outcomes in psychotherapy. However, little is known as to how this applies to psychotherapies which reduce suicidal experiences. The current narrative review summarizes the literature which investigates the relationship between the therapeutic alliance in psychotherapy and a range of suicidal experiences prior to, during and following psychotherapy. Systematic searches of MEDLINE, PsycINFO, Web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 116 publications
0
7
0
Order By: Relevance
“…Systematic research has shown an association between a strong therapeutic alliance and fewer suicidal thoughts; this finding was reported in longitudinal studies in which the alliance with a mental health professional was evaluated 35. The therapeutic alliance, therefore, requires special attention when treating patients with some level of suicidality 36…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Systematic research has shown an association between a strong therapeutic alliance and fewer suicidal thoughts; this finding was reported in longitudinal studies in which the alliance with a mental health professional was evaluated 35. The therapeutic alliance, therefore, requires special attention when treating patients with some level of suicidality 36…”
Section: Discussionmentioning
confidence: 98%
“…35 The therapeutic alliance, therefore, requires special attention when treating patients with some level of suicidality. 36…”
Section: Discussionmentioning
confidence: 99%
“…Hence, some mothers might have never received the support of a therapist and could not therefore draw on that experience to assist them in their judgement of how important the therapeutic alliance might be to the outcome of an intervention. Furthermore, a recent systematic review of 19 quantitative studies summarised the relationship between the therapeutic alliance in psychotherapy and suicidal experiences prior to, during and following psychotherapy ( 52 ). The authors failed to identify a significant association between suicidal experiences prior to, or during, the psychotherapy and the strength of the therapeutic alliance.…”
Section: Discussionmentioning
confidence: 99%
“…In a related domain, countertransference, what has been broadly conceptualized as the therapist's emotional reactions to the therapeutic encounter (Gelso & Kline, 2022), has also been shown to be more negative when therapists are working with suicidal patients (Barzilay et al, 2020) and that these adverse countertransference patterns may impact suicide outcomes (Michaud et al, 2021). While therapeutic alliance and counter transference are known to impact suicide prevention (Dunster‐Page et al, 2017; Huggett et al, 2022), effectively measuring this impact over time remains difficult (Ryu et al, 2021; Tishby & Wiseman, 2022).…”
Section: Introductionmentioning
confidence: 99%